1987
DOI: 10.1159/000124732
|View full text |Cite
|
Sign up to set email alerts
|

Dopaminergic and Cholinergic Influences on the Growth Hormone Response to Growth Hormone-Releasing Hormone in Man

Abstract: It is well established that compounds that modify dopaminergic and cholinergic activity in man may induce changes in circulating growth hormone (GH). We have, therefore, investigated the effect of a dopamine agonist, bromocriptine, and a dopamine antagonist, domperidone, as well as a muscarinic cholinergic antagonist, pirenzepine, on the GH response to an analogue of GH-releasing hormone (GHRH) in normal male subjects. GHRH(1–29)NH2 induced a rise in serum GH that was augmented by bromocriptine, ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0
2

Year Published

1989
1989
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 17 publications
1
18
0
2
Order By: Relevance
“…The time elapsed from when bromocriptine was given in these studies [6,8] and when its GH-secreting effects were observed are both compatible with that observation [35] and our hypothesis on adrenergic-mediated central effects of DA on SS secretion. It would be interest ing to test GH responses to GHRH given at shorter intervals following bromocriptine administration.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The time elapsed from when bromocriptine was given in these studies [6,8] and when its GH-secreting effects were observed are both compatible with that observation [35] and our hypothesis on adrenergic-mediated central effects of DA on SS secretion. It would be interest ing to test GH responses to GHRH given at shorter intervals following bromocriptine administration.…”
Section: Discussionsupporting
confidence: 89%
“…This hypothesis is not inconsistent with the demonstration that DA and bromocriptine augmented the GHRH-induced GH response in normal man [6,8], In these studies, bromocrip tine administration induced a spontaneous GH secretion begin ning 90 min later. GHRH challenge at these times elicited a significant GH release in both experiments.…”
Section: Discussionmentioning
confidence: 48%
“…In the last few years a large body of both direct and circum stantial evidence has established that acetylcholine regulates GH secretion by tonically inhibiting somatostatin release by the hypothalamus [9,10,20,21 ]. In agreement with this hypothesis, the inhibitory feedback exerted by GH and GHRH on GH se cretion can be overcome by cholinergic activation by pyridostig mine and the resulting blockade of somatostatin release [ 10,22,23).…”
Section: Discussionmentioning
confidence: 87%
“…Similarly, the GH responsive ness to GHRH bolus injection is clearly enhanced by bromo criptine pretreatment [7, 31 ]. The conclusion from these studies was that, in the presence of a pharmacological dose of GHRH, enhanced GH release during dopaminergic stimulation oc curred by a reduction in hypothalamic somatostatin release.…”
Section: Discussionmentioning
confidence: 99%